Defining Phenotypic Causes of Obstructive Sleep Apnea. Identification of Novel Therapeutic Targets - Eckert, Danny J.; White, David P.; Jordan, Amy S.; Malhotra, Atul; Wellman, Andrew (American journal of respiratory and critical care medicine, 2013)
The pathophysiologic causes of obstructive sleep apnea (OSA) likely vary among patients but have not been well characterized. To define carefully the proportion of key anatomic and nonanatomic contributions in a relatively large cohort of patients with OSA and control subjects to identify pathophysiologic targets for future novel therapies for OSA. Seventy-five men and women with and without OSA aged 20-65 years were studied on three separate nights. Initially, the apnea-hypopnea index was determined by polysomnography followed by determination of anatomic (passive critical closing pressure of the upper airway [Pcrit]) and nonanatomic (genioglossus muscle responsiveness, arousal threshold, and respiratory control stability; loop gain) contributions to OSA. Pathophysiologic traits varied substantially among participants. A total of 36% of patients with OSA had minimal genioglossus muscle responsiveness during sleep, 37% had a low arousal threshold, and 36% had high loop gain. A total of 28% had multiple nonanatomic features. Although overall the upper airway was more collapsible in patients with OSA (Pcrit, 0.3 [-1.5 to 1.9] vs. -6.2 [-12.4 to -3.6] cm H2O; P <0.01), 19% had a relatively noncollapsible upper airway similar to many of the control subjects (Pcrit, -2 to -5 cm H2O). In these patients, loop gain was almost twice as high as patients with a Pcrit greater than -2 cm H2O (-5.9 [-8.8 to -4.5] vs. -3.2 [-4.8 to -2.4] dimensionless; P = 0.01). A three-point scale for weighting the relative contribution of the traits is proposed. It suggests that nonanatomic features play an important role in 56% of patients with OSA. This study confirms that OSA is a heterogeneous disorder. Although Pcrit-anatomy is an important determinant, abnormalities in nonanatomic traits are also present in most patients with OSA.